Górnośląska misja Wojciecha Stpiczyńskiego. Z działalności piłsudczyków w okresie powstań i plebiscytu (1920-1921) - Pietrzak, Jacek (Acta Universitatis Lodziensis. Folia Historica, 1999)
A problem of the interior struggle for political influence on the Polish liberation movement in the Upper Silesia in the period of Silesian’s uprisings and plebiscite, and closely connected to it a question of the relations between the Polish political and military authorities and the insurgent movement awakes more and more interest of the historians. Wojciech Stpiczyński – a main hero of this article – as a commander of the plebiscite’s team of the military secret service (Department „B” of the 2nd Department of the Staff of the Ministry of Military Affairs) played an important part in the government’s action of support to the military movement in conspiracy in the Upper Silesia and later – as a delegate of government – to the 3rd Silesian uprising. His activity as an unofficial political emissary of the Piłsudski’s camp (called also – belwederski) in the Upper Silesia is worth noticing. It was specially important at the finally phase of the 3rd Silesian uprising and just after the end of insurrection. Stpiczyński, as an organiser and then an effective political head of the Association of the Former Insurgents (Związek Byłych Powstańców – ZPB) – which constituted a kind of continuation of the military organisation, tried to paralyse the influences of the Christian- Democratic political camp and National-Democratic one in Silesia. He was considered by them as a main person responsible for the realisation of the Pilsudski’s policy in Silesia, and due to that fact he was attacked very strongly by the press connected with those camps because of the abuses of the military intelligence service in the autumn 1921. In spite of the mission had been over in the end of 1921, Stpiczyński managed to play an important role in the establishing of Piłsudski’s supporters influence among the former Silesian insurgents.